Effects of Preoperative and Perioperative Administration of Wobenzym Vital on Minimal-Mild Endometriosis. Issue 2 (April 2015) - Giannini, Andrea; Palla, Giulia; Goglia, Lorenzo; Genazzani, Andrea R.; Genazzani, Alessandro; Simoncini, Tommaso
Background: Endometriosis is an estrogen-dependent chronic inflammatory disease associated with pelvic pain, inflammation and infertility. Drugs that modulate the release of chemokines and angiogenic and inflammatory molecules are under evaluation. The aim of the present randomized, double-blind, placebo-controlled study was to investigate the effects of Wobenzym Vital, an enzyme-flavonoids combination supplement with antiinflammatory activity, as supportive treatment in patients affected by minimal-moderate endometriosis selected for surgery. Methods: Thirty women suspected for endometriosis stage I-II were randomly assigned to receive Wobenzym Vital or placebo for a period of 40-60 days before surgery and 60 days thereafter. Visual analog scale (VAS) scores for pain at enrollment, time of surgery and 7 and 60 days afterwards were evaluated. Blood samples were taken at the same times for the assay of several inflammatory, angiogenic and growth factors and growth factor regulators. Results: Treatment with Wobenzym Vital was associated with lower VAS scores before surgery and perioperatively. Surgery further reduced VAS scores in all patients. Patients receiving placebo underwent increases in plasmatic concentrations of sCD40L, EGF, IGFBP-1, IL-6, IL-8, TGF-α and TNF-α in the perioperative period, while this was not noted in patients with active treatment. A trend for lower concentrations of several of the tested analytes in the peritoneal fluid was found in patients treated with Wobenzym Vital. Conclusions: In symptomatic patients affected by minimal-mild endometriosis undergoing surgery, preoperative and postoperative treatment with Wobenzym Vital results in reduced pain and lower concentrations of inflammatory and angiogenic factors in peripheral blood and the peritoneal cavity.